Participation in groups as indicator of social capital of adolescents workers - Campos, Ana Cristina Viana; Borges, Carolina Marques; Zarzar, Patrícia Maria Pereira de Araújo; Lucas, Simone Dutra; Vagas, Andrea Maria Duarte; Ferreira e Ferreira, Efigênia (Revista de Psicologia, 2013)
The aim of this study was to evaluate the potential of participation in groups as a single variable to measure the social capital of young workers. We conducted a transverse analytical study with 363 adolescent workers assisted by a Supreme Philanthropic Support Teen by the application of the Integrated Questionnaire for Measuring Social Capital (SC-IQ). We considered two different types of classification of capital stock that were compared by analyzing nearest neighbor interpolation on the questions selected from the survey. It was concluded that participation in groups cannot be considered a good indicator of social capital in the study sample. The friendship was measured by the number of friends, along with trust and collective action aspects are good measures of capital stock.